Direct Mannich‐Type Reactions Promoted by Frustrated Lewis Acid/Brønsted Base Catalysts. (30th September 2016) - Chan, Jessica Z.; Yao, Wenzhi; Hastings, Brian T.; Lok, Charles K.; Wasa, Masayuki
Abstract: Direct Mannich‐type reactions that afford both α‐ and β‐amino esters by the reaction of a broad range of carbonyl compounds and aldimines are disclosed. The transformation is promoted by a sterically frustrated Lewis acid/Brønsted base pair, which is proposed to operate cooperatively: Within the catalyst complex, an enolate is generated that then reacts with a hydrogen‐bond‐activated imine. Noncovalent interactions between reactants and the catalyst provide selectivity and new opportunities for future catalyst design.